Design and Implementation of an IoT-Based Automatic Irrigation and Monitoring System for Bird’s Eye Chili Plants with Telegram and Blynk Platform Integration - Ellys Kumala Pramartaningthyas; Siti Ma’shumah; Abdullah Al Hannan (Universitas Islam Raden Rahmat, Malang, 2025)
The development of an Internet of Things (IoT)-based automatic watering and monitoring system for cayenne pepper plants, integrated with Telegram, aims to simplify the process of maintaining optimal soil moisture levels. By enabling real-time monitoring via smartphones, this system helps ensure that plants receive adequate water without experiencing overwatering or drought stress. The system utilizes a capacitive soil moisture sensor to detect moisture levels and a NodeMCU ESP8266 microcontroller, which includes an integrated WiFi module, for network connectivity. A relay module is used to control the water pump based on sensor readings. Experimental results—detailed in Chapter IV—demonstrate that the system operates effectively, as reflected by successful automatic irrigation and timely notification delivery through Telegram. Furthermore, the system's performance, evaluated in accordance with Telecommunications and Internet Protocol Harmonization Over Networks (TIPHON) standards, recorded average communication delays of 2.0 seconds and 2.5 seconds respectively. These results support the claim of reliable and responsive system communication, as further substantiated by the performance data presented in the results section.